2021
DOI: 10.1111/exsy.12837
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy expert system for road type identification and risk assessment of conventional two‐lane roads

Abstract: This paper first presents a fuzzy expert system to identify and classify conventional two‐lane roads based on geometric characteristics. Both fuzzy and neuro‐fuzzy techniques have been used. Fuzzy logic has proved suitable to address this problem, since in this case, there is a variability of input information, and classical rules are not suitable to be used due to the uncertainty introduced by some combinations of the variables. Each road's geometric features were measured by sensors in an equipped vehicle, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Bearing the above results in mind, it can be concluded that the proposed model can be used to assess the respondents' tendency to participate in road crashes. The above results show another application of fuzzy logic, in addition to its already proven useful application in many areas [33][34][35][36][37][38], ordered recently.…”
Section: Discussionmentioning
confidence: 62%
“…Bearing the above results in mind, it can be concluded that the proposed model can be used to assess the respondents' tendency to participate in road crashes. The above results show another application of fuzzy logic, in addition to its already proven useful application in many areas [33][34][35][36][37][38], ordered recently.…”
Section: Discussionmentioning
confidence: 62%
“…But this classification may be no longer appropriate due to the degradation of the road, which may cause changes in some of its geometric characteristics (Barreno et al, 2021). This is relevant because speed limit is usually set based on the road design features.…”
Section: Simulation and Discussion Of Resultsmentioning
confidence: 99%
“…Road infrastructure geometry and state may both influence driving safety through their perception by the drivers. Driver behaviour as well as road geometry and condition are the most important factors in the safety and comfort of the trip [4,5]. Specifically, the critical acceleration due to the influence of the road geometry can be measured with inertial sensors and then used with the lateral acceleration to estimate the driver's perceived acceleration.…”
Section: Introductionmentioning
confidence: 99%